First hospital outbreak of the globally emerging Candida auris in a European hospital. Issue 1 (December 2016) - Schelenz, Silke; Hagen, Ferry; Rhodes, Johanna; Abdolrasouli, Alireza; Chowdhary, Anuradha; Hall, Anne; Ryan, Lisa; Shackleton, Joanne; Trimlett, Richard; Meis, Jacques; Armstrong-James, Darius; Fisher, Matthew
Abstract Background Candida auris is a globally emerging multidrug resistant fungal pathogen causing nosocomial transmission. We report an ongoing outbreak ofC. auris in a London cardio-thoracic center between April 2015 and July 2016. This is the first report ofC. auris in Europe and the largest outbreak so far. We describe the identification, investigation and implementation of control measures. Methods Data onC. auris case demographics, environmental screening, implementation of infection prevention/control measures, and antifungal susceptibility of patient isolates were prospectively recorded then analysed retrospectively. Speciation ofC. aur is was performed by MALDI-TOF and typing of outbreak isolates performed by amplified fragment length polymorphism (AFLP). Results This report describes an ongoing outbreak of 50C. auris cases over the first 16 month (April 2015 to July 2016) within a single Hospital Trust in London. A total of 44 % (n  = 22/50) patients developed possible or provenC. auris infection with a candidaemia rate of 18 % (n  = 9/50). Environmental sampling showed persistent presence of the yeast around bed space areas. Implementation of strict infection and prevention control measures included: isolation of cases and their contacts, wearing of personal protective clothing by health care workers, screening of patients on affected wards, skin decontamination with chlorhexidine, environmental cleaning with chorine based reagents and hydrogen peroxide vapour. Genotyping with AFLP demonstrated thatC. auris isolates from the same geographic region clustered. Conclusion This ongoing outbreak with genotypically closely relatedC. auris highlights the importance of appropriate species identification and rapid detection of cases in order to contain hospital acquired transmission.